2022
DOI: 10.3390/su14148659
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Residential Photovoltaic Promotion Policy on Installation Intention in Typical Regions of China

Abstract: Increasing the popularity of distributed photovoltaic technology among Chinese residents is of great significance to achieve the dual carbon goal (emission peak and carbon neutrality). In this study, we collected 1424 questionnaire samples and used PLS-SEM for group modeling and comparative analysis of bungalow and building residents. The results show that living conditions, costs, risks of installation, maintenance, and economic efficiency are the five significant influencing factors for residents to decide w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 66 publications
0
5
1
Order By: Relevance
“…These findings align with previous research and have practical implications for the Chinese government's PV subsidy policies. For instance, Wang et al [ 24 ] and Wang et al [ 58 ] mentioned this phenomenon in their research [ 24 , 58 ], indicating that to further promote residential PV at the current stage, economic incentive policies, such as subsidies, still need to be prioritized. Li et al [ 75 ] believe that publicity and guidance can also improve residents' willingness to install.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings align with previous research and have practical implications for the Chinese government's PV subsidy policies. For instance, Wang et al [ 24 ] and Wang et al [ 58 ] mentioned this phenomenon in their research [ 24 , 58 ], indicating that to further promote residential PV at the current stage, economic incentive policies, such as subsidies, still need to be prioritized. Li et al [ 75 ] believe that publicity and guidance can also improve residents' willingness to install.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, residential PV equipment cannot be installed independently (a decision must be made by the owners' meeting in accordance with Chinese law). Previous studies by Wang et al [ 58 ] and Wang et al [ 24 ] explained the complexity of building residents installing residential PV using the theory of psychological distance and the TAM model, respectively. They suggested that building residents might have a more distant perception of residential PV and face challenges owing to incomplete property rights.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations